City Policies and the European Urban Agenda
XXIX, 350 p. 25 illus.
Keywords: During the next few years, most European and World cities will be developing urban agendas. Materials published on the subject have been relatively scarce until now. This edited volume introduces a case study implementation of the European Urban Agenda (EUA) in a cross-border region in the Iberian Peninsula between Spain (Galicia) and Portugal. It explores the implementation of a number of urban core principles in two distinctive regions, serving as the basis for a comparative analysis on how such galvanizing principles work, contained in the EUA. The case presented in this edited volume is the first cross-border urban agenda to be drafted. It is a unique piece that contributes to our understanding of the complexities of implementing and translating a common set of urban European principles to variety of different local milieus. The chapters of the book closely examine the various strands of the implementation of urban policies through the lenses of land use, economic competition,innovation, culture and creative industries, energy, ecology, demographic challenges, housing, social inclusion and democratic governance. These chapters are written by international renowned scholars who were involved in the drawing up of the urban agenda for this territory. The ideas, principles and concepts that they impart can be extrapolated to most cities. Martín Fernández-Prado is Professor of Urban Design and Territorial Planning at the School of Architecture, University of A Coruña, Spain. He is a member of the study group of the Eixo Atlántico del Noroeste Peninsular (EANP) and a co-director of the Eixo Atlántico Urban Agenda (EAUA). He has studied Architecture and Urban Design at Harvard University. Luis Domínguez Castro is Professor and Jean Monnet Chair Ad Personam of EU History and Territorial Cooperation, and Coordinator of the Jean Monnet Cross-Border European Centre of Excellence at the University of Vigo, Spain. He is also a member of the study group of the Eixo Atlántico del Noroeste Peninsular and a co-director of the Eixo Atlántico Urban Agenda.